Improving Motivation to Learn Social Studies Through the Problem-Based Learning Introduction (PBI) Model for Elementary School Students - Tomi Tri Arrahman (Council: Education Journal of Social Studies, 2026)
This study aims to improve students' learning motivation by improving the Problem-Based Introduction (PBI) model in grade V students of SDN 1 Bakung. The research method used is Classroom Action Research. This study was conducted in two action cycles. each planning and implementation in two action cycles. Each cycle consists of six meetings. The study found that using the Problem-Based Introduction Model can improve students' learning motivation. The increase was based on the results of the pre-action, which showed that students had not shown motivation in learning, such as students paying attention to the teacher when explaining the material, students dared to ask questions if they did not understand, and more and more students did not hesitate to ask, if they did not understand, and give opinions during group discussions. In cycle II, the increase was more maximal, and more and more students did not hesitate to ask questions in expressing their opinions. And students answered that the increase was also seen in the percentage of students' learning motivation. The percentage of students' learning motivation in cycle I was 58.3% and in cycle II was 92%. So that students' learning motivation in cycle I and cycle II was presented at 33.7%, thus the PBI model can improve students' learning motivation.